Application of RHA’s Pozzolanic Properties in the Making of CEB - Riza, Fetra Venny (International Journal of Sustainable Construction Engineering and Technology, 2022)
The production of Compressed Earth Brick (CEB) does not require burning as compared to normal clay brick. However it requires cement to stabilize and bind the clay into brick. This study tried to replace cement with Rice Husk Ash (RHA) as a binding material in the making of CEB. Since RHA is commonly used as a pozzolanic material in strengthening concrete where it react with calcium hydroxide generated from the cement hydration, this study used hydrated lime to mix with RHA to produce the same pozzolanic reaction. The result shows that the mixture with combination 25% RHA and 75% hydrated lime give the best result. Even though the strength do not reach the standard set by MS76 for load bearing brick, however it could be used as non load bearing brick.